Extending Juran’s Quality Trilogy in Islamic Boarding Schools: Empirical Insights for Realizing SDG 4 in Indonesia - Matnasir Matnasir; Sujarwanto Sujarwanto; Nunuk Hariyati (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: To examine how pesantren-based schools institutionalize quality management by implementing Juran’s Quality Trilogy through an embedded organizational quality culture. It addresses the limited understanding of how quality planning, quality control, and quality improvement are integrated within faith-based educational institutions. Method: Employing a qualitative multisite case study involving two Indonesian secondary schools integrating the national education system with the pesantren tradition. Data were collected through in-depth interviews with school leaders, teachers, administrative staff, students, parents, and education authorities, supported by observations and document analysis. The data were analyzed using within-case and cross-case thematic analysis, while triangulation and member checking ensured trustworthiness. Results: The findings indicate that quality planning was collaboratively developed through stakeholder participation, curriculum integration, and shared educational values. Quality control was sustained through continuous academic supervision, religious discipline, routine monitoring, and collective responsibility. Quality improvement was achieved through institutional learning, collaborative professional development, and reflective evaluation embedded in daily practices. These processes were integrated through Pesantren Quality Culture, which functioned as the organizational mechanism connecting the three dimensions of Juran’s Quality Trilogy into a continuous quality management cycle. Novelty: Proposing a contextual quality management model for faith-based schools by extending Juran’s Quality Trilogy through Pesantren Quality Culture. The model highlights the integration of shared religious values, stakeholder collaboration, continuous organizational learning, reflective evaluation, and collective commitment as key drivers of sustainable educational quality for SDG 4.